A conceptual model for the professional profile of a data scientist - Costa, Carlos (2017)
Data-driven web applications support most of the activities in our current world, built upon databases and data services. Consequently, the Data Scientist emerges as a role of major importance, extracting value from data and creating even more data products with increased value. The term Data Scientist attracted a lot of attention during the last years, becoming relevant to understand its origin, knowledge base and skills set, in order to adequately describe its profile and distinguish it from others, such as Business Analyst. This work proposes a conceptual model for the professional profile of a Data Scientist, showing that a significant part of its knowledge base and skills set are related with Information and Communications Technology (ICT), including program- ming, machine learning and databases, and also with areas such as computer science, statistics, mathematics and information systems.